Interaction of water with a benzimidazole derivative: fluorescence and colorimetric recognition of trace level water involving intra‐molecular charge transfer process. Issue 1 (31st July 2015) - Nandi, Sandip; Mandal, Sandip; Matalobos, Jesus Sanmartin; Sahana, Animesh; Das, Debasis
Abstract : Benzimidazole‐derived ICT‐based probe, DFPBEN is developed for trace level determination of water. In presence of water, the naked eye color of DFPBEN changes from red to yellow, while it turns to green from red under UV light. Upon addition of water, DFPBEN shows a ratiometric absorbance change in methanol. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Single crystal X‐ray structurally characterized, ICT‐based ratiometric fluorescence probe (DFPBEN ) changes color in presence of traces water from red to yellow without UV excitation while red to green under UV light.